1968
DOI: 10.1103/physrev.175.868
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Measurement of Clustering in the Alloy CuNi

Abstract: Measurements have been made of the cluster diffuse neutron scattering from a polycrystalline sample of Cuo.52sNi 62 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1971
1971
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…The existence of atomic and/or magnetic clustering in Ni-Cu alloys has been reported by many investigators since the prediction of a miscibility gap in this system by Meijering(10) Diffuse neutron scattering measurements by Mozer et al (11) in the Ni-Cu system, which gives high accuracy by such an advantage that the coherent Bragg scattering cross-section is reduced to zero ("null matrix") due to the negative scattering length of the isotope 62Ni, have first established this short-range clustering suggested. Recent neutron diffraction studies on the null matrix Ni-Cu alloys have reported a strong asymmetry in the composition dependence of cluster parameters, the existence of a miscibility gap at temperatures below 600 K (12), and the formation of periodic concentration, which is expected for the spinodal decomposition, under irradiation (13) In metallic crystals, the electrical resistivity sensitively reflects not only the magnetic property and the electronic structure but also slight defect of atomic arrangement (14).…”
Section: Introductionmentioning
confidence: 82%
“…The existence of atomic and/or magnetic clustering in Ni-Cu alloys has been reported by many investigators since the prediction of a miscibility gap in this system by Meijering(10) Diffuse neutron scattering measurements by Mozer et al (11) in the Ni-Cu system, which gives high accuracy by such an advantage that the coherent Bragg scattering cross-section is reduced to zero ("null matrix") due to the negative scattering length of the isotope 62Ni, have first established this short-range clustering suggested. Recent neutron diffraction studies on the null matrix Ni-Cu alloys have reported a strong asymmetry in the composition dependence of cluster parameters, the existence of a miscibility gap at temperatures below 600 K (12), and the formation of periodic concentration, which is expected for the spinodal decomposition, under irradiation (13) In metallic crystals, the electrical resistivity sensitively reflects not only the magnetic property and the electronic structure but also slight defect of atomic arrangement (14).…”
Section: Introductionmentioning
confidence: 82%
“…However, this phase transformation gives no remarkable influence on the ferromagnetic property in this alloy (12). In the NiCo alloys, the average magnetic moment increases linearly with increasing Co contents, since the up-spin band is fully occupied over the whole concentration range (14 (17). In the present work, the experimental results of the electrical resistivity measurements in nickel, cobalt and their alloys are reported in detail and are discussed in connection with their magnetic properties.…”
mentioning
confidence: 87%
“…Од-нак, при дослідженні ядерного розсіяння теплових нейтронів можна підібрати ізотопічний склад сплаву таким чином, щоб для атомів А і В амплітуди розсіяння b A і b B мали різні знаки і середня амплітуда розсі-яння перетворювалась в нуль (тобто, щоб бреґґівські піки зникли, а ін- [2,128]. Цей метод «нульової матриці» було застосовано для дослідження розпадаючогося сплаву Cu-Ni [29][30][31] з ізотопами 62 Cu і 62 Ni, що дозволило отримати достатньо точні і узгоджені результати (для однакових рівноважних станів), навіть при використанні дебаєвської методики розсіяння на полікристалічних зразках (спотворення в Cu-Ni незначні і могли не враховуватися). Для складу, відповідного «нульовій матриці» (з 43,5 ат.% та 41,4 ат.% Cu), отримані результати приведено в табл.…”
Section: параметри кореляціїunclassified
“…Враховувалась далекосяжна кулонівська взаємодія та ефекти поляризації іонів O (бу-ло показано, що для отримання реалістичної картини опису впорядку-вання тетраедричних катіонів необхідно враховувати обидва фактори). Для рівноважних розподілів 29 Si/Al проаналізованих складів (1  29 Si/Al   3) було виявлено близький порядок.…”
Section: 4unclassified